The Study on the Design Characteristics, Craftsmanship, and Modern Application of Bamboo Chairs in Southwest China in the 20th Century - Shu, Xingchuan; Joenurairatana , Eakachat (Journal of Roi Kaensarn Academi, 2024)
This research aims to explore the design characteristics, craftsmanship, and modern applications of bamboo chairs in Southwest China during the 20th century. The study focuses on a selected sample of bamboo chairs from various regions within Southwest China, including Sichuan, Yunnan, and Guizhou provinces, known for their rich traditions in bamboo craftsmanship. Research instruments include field investigations, literature analysis, and case studies. Data collection was conducted through on-site observations, interviews with local artisans, and the analysis of historical documents and existing research. Data analysis involved qualitative analysis and descriptive statistics to identify patterns, trends, and unique features in bamboo chair design and craftsmanship. The research results found that bamboo chairs from Southwest China exhibit distinct regional characteristics, combining practical design with deep cultural significance. The use of sustainable bamboo materials, traditional mortise-and-tenon joints, and intricate decorative techniques were highlighted as key elements that contribute to the enduring appeal and functionality of these chairs. Additionally, the study suggests that modern applications of bamboo chairs can be enhanced by integrating traditional craftsmanship with contemporary design principles, promoting both cultural preservation and innovation in furniture design.